Електронна періодика у системі наукової комунікації: особливості становлення та функціонування - Рижко, Ірина В.; Ryzhko, I. V. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті досліджено специфічний вид наукової періодики – мережеві наукові часописи. Розглянуто цілісну картину еволюції он-лайнового наукового журналу, проаналізовано передумови виникнення та історію розвитку електронної форми наукової періодики з точки зору світових тенденцій. Вивчено сприйняття дослідниками електронних наукових періодичних видань на різних етапах їх становлення. З’ясовано роль та місце електронної періодики у сучасній системі наукової комунікації. The article studied the specific kind of scientific periodicals – network science journals. Considered a complete picture of the evolution of online scientific journal, analyzed predictors of history and the development of electronic forms of scientific periodicals in terms of global trends. Researchers studied the perception of electronic scientific periodicals at different stages of their development. Clarify the role and place of electronic periodicals in the modern system of scientific communication. We proved that the transformation of the form of the scientific journal in connection with the advent of the Internet has contributed to opening new horizons in the information support of science, the discovery of new resources, forms of organization and research activities, as well as led to the creation of new and very sophisticated search engine, links, access control, distribution and licensing.
Electronic Periodicals in the System of Scientific Communication: Formation and Functioning
Keywords: електронна наукова періодика; electronic scientific periodicals; мережевий науковий простір; scientific space network; он-лайнові наукові ресурси; online research resources; наукова комунікація; scientific communication; відкритий доступ; open access